Estresses de temperatura e concentrações de acetosiringona na transformação genética de milho via Agrobacterium tumefaciens - Teixeira, Tiago (2017)
To establish the technique of plant genetic transformation by A. tumefaciens, one of the critical points is to adjust the factors affecting the transformation, such as plant genotype and conditions of infection and co-culture of the explants by applying strategies that can increase the frequency of the T-DNA transference, such as the stress application before and during the explant infection with agrobacteria and adjustment of the phenolic compound concentration in the infection and co-culture media. Therefore, this work aimed at adjusting a protocol of genetic transformation by A. tumefaciens for two maize genotypes. The first chapter of this work evaluate the effect of different infection conditions applied to immature embryos of the Hi-II hybrid and the BR451 Brazilian variety with A. tumefaciens EHA101:pTF101, carrying the bar and uidA genes under control of CaMV35S promoter. In the first experiment the embryos were submitted to different temperatures of infection (43oC and room temperature). In the second experiment was applied a combined stress (46oC per 3 minutes, cooling in ice per 1 minute, centrifugation 12.000 rpm at 4oC per 10 minutes) before the infection with. A. tumefaciens. In the second chapter are described the experiments referring to the effect of different concentration of acetosyringone in the infection medium (Assay 1) and the same concentration supplemented in the infection and also in the co-culture media (Assay 2). The tested acetosyringone concentrations were: 0 µM (control), 100 µM, 200µM, 400µM and 600µM. The transient transformation frequency was evaluated by the GUS histochemical assay, which shows the uidA report gene expression in the plant transformed tissue. The frequency of stable transformation was evaluated through the expression of the bar marker gene. There was positive effect of the high temperature in the intensity of the uidA reporter gene. Combined stress applied before the infection resulted in approximately 50% mortality of embryos, reducing the efficiency of transformation of the Hi-II genotype. Acetosyringone is of extreme importance in the co-culture for the transference of the T-DNA. The Hi-II genotype was affected by the concentration when applied only in infection phase, while genotype BR 451 was not influenced by that. The acetosyringone concentrations applied to the infection and coculture media influenced the transient transformation of the two genotypes and the dose of 400µM of revealed to be more efficient for the transient transformation of immature embryos of HiII and BR451maize of genotypes. The variety BR 451 showed capacity of being transformed, but in a lower frequency compared to the Hi-II hybrid.